Dampak Lembaga Pembiayaan pada Usaha dan Kesejahteraan Masyarakat Kabupaten Tangerang - Kusdiana, Dikdik (Jurnal Trikonomika, 2008)
Characteristics which is owned by small enterprise signs some weakness to access banking service. One of the characteristic, collateral, has been an important barrier to access banking service, so they require some ways to improve their access. LPP-UMKM is an alternative way to solve the problem. This paper aims to describe the impacts of a micro credit program (LPP-UMKM) to Small enterprise empowerment and wellfare. This research used primary data. The data gained from survey to 100 small entreprises, with paired different sample test. The paired different sample test with 95% degree of significancy proved that existence of LPP-UMKM have had an effect on to small enterprise business and their welfare. From study result can be conclused that micro credit program(LPP-UMKM) have been improved marketing, financial and production aspect of small enterprise and also it have been increased welfare society of 5 district in Kabupaten Tangerang.